Sleep Duration and Parenting Styles' Effects on Children's Development and Growth - Nabila Retno Putri Budiyanto; Lilik Ariyanti; Sevy Astriyana (Indonesian Journal of Global Health Research, 2024)
Continuous growth and development, several influencing factors are sleep duration and parenting style. Children's mental, physical, and emotional health all depend on getting enough good sleep. Academic success, emotional control, and overall well-being are all enhanced by getting enough sleep. The purpose of this research is to ascertain whether parenting styles and sleep duration have an impact on the growth and development of children. Cross-sectional study design was used. The Denver Development Screening Test sheet, the Pittsburgh Sleep Quality Index (PSQI), and the Parenting Styles and Dimensions Questionnaire (PSDQ) were the measurement tools utilized. There were twenty-one children in the sample, ages four to five. Purposive sampling was used in the sampling procedure. Statistical test results of sleep duration with growth (p value: 0.323), sleep duration with development (p value: 0.696), parenting style with growth (p value: 0.247) and parenting patterns with development (p value: 0.497). There is no relationship between sleep duration and parenting style on the growth and development of children aged 4-5 years.